DEVELOPMENT OF MARKETPLACES IN THE CONTEXT OF DIGITAL TRANSFORMATION AS A RESULT OF STRUCTURAL SHIFTS IN THE ECONOMY - E. S. Vorobeva; Z. A. Yusubova; M. A. Gasanov (Вестник университета, 2021)
Globalization and increased volatility of global markets, as well as increased competition, lead to the need for the business community to create new sustainable business models that are less susceptible to the negative effects of globalization. The sustainability of business models is determined by the effective use of resources: natural, material, financial and intellectual. The result of the transformation is the transition to network interaction and the formation of ecosystems of suppliers, partners, consumers and competitors around the business sphere. The main conclusions of the research paper are reduced to the need to achieve a comprehensive development of the digital economy, taking into account the interrelationships of economic processes and structural transformations. In this regard, the analysis of the relationship and principles of structural shifts in economic processes against the background of digital transformation becomes particularly relevant.